PENGARUH INKUIRI TERBIMBING TERHADAP HASIL BELAJAR RANAH KOGNITIF DAN KETERAMPILAN GENERIK SAINS - Vidya Artha Savitrie; Berti Yolida; Rini Rita T Marpaung (Universitas Lampung, 2015)
The purpose of this research was to know the influence of guided inquiry learning model to students cognitive learning outcomes and science generic skills (SGS). The samples were students of SMAN 1 Tumijajar that were chosen by purposive sampling technique. The quantitative data were students learning outcomes and SGS. The qualitative data were observation result of SGS and responses. The results were students cognitive indicators (C2, C3, C4, C6) of experiment class with average N-gain which was 58,00 that different significantly and higher than control class which was 39,70, only C5 indicator that was not different. Average N-gain of SGS from experiment class 68,76 which was different significantly and higher than control class which was 35,28. Most of students (88.23%) gave positive responses. Thus, the application of guided inquiry learning model could improve cognitive learning outcomes and SGS of students in the subject matter of Ecosystem.Penelitian ini bertujuan mengetahui pengaruh model pembelajaran inkuiri terbimbing terhadap hasil belajar kognitif dan Keterampilan Generik Sains (KGS) siswa. Sampel adalah siswa SMAN 1 Tumijajar dipilih secara purposive sampling. Data kuantitatif berupa hasil belajar kognitif dan KGS. Data kualitatif berupa observasi KGS dan tanggapan siswa. Hasil belajar kognitif siswa kelas eksperimen dengan rata-rata N-gain (58,00) berbeda signifikan dan lebih tinggi dari kelas kontrol (39,70). Rata-rata N-gain indikator soal C2, C3,C4, C5 dan C6 kelas eksperimen lebih tinggi. Hanya pada indikator C5 berbeda tidak signifikan. KGS siswa kelas eksperimen dengan rata-rata N-gain (68,76) berbeda signifikan dengan kelas kontrol (35,28). Sebagian besar siswa (88,23%) memberikan tanggapan positif. Sehingga, penerapan model pembelajaran inkuiri terbimbing dapat meningkatkan hasil belajar kognitif dan KGS siswa pada materi pokok Ekosistem.Kata kunci : inkuiri terbimbing, keterampilan generik sains, ranah kognitif